2020
DOI: 10.1186/s13195-020-00705-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, neuromorphological, and neurobiochemical effects induced by omega-3 fatty acids following basal forebrain cholinergic depletion in aged mice

Abstract: Background In recent years, mechanistic, epidemiologic, and interventional studies have indicated beneficial effects of omega-3 polyunsaturated fatty acids (n-3 PUFA) against brain aging and age-related cognitive decline, with the most consistent effects against Alzheimer’s disease (AD) confined especially in the early or prodromal stages of the pathology. In the present study, we investigated the action of n-3 PUFA supplementation on behavioral performances and hippocampal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 161 publications
(240 reference statements)
0
8
0
Order By: Relevance
“…These cellular changes were associated with the amelioration of spatial and recognition memory skills in these animals [73]. Hippocampal astrogliosis was also reduced by a LCPUFA combination of DHA, EPA and n-3 docosapentaenoic acid (DPA) supplementation in aged male mice with forebrain cholinergic depletion, in correlation with recognition memory restoration [107]. The beneficial effect of n-3 LCPUFA in reverting the inflammatory scenario appears to be also achieved with specific individual n-3 LCPUFA species; thus, in a rat neuroinflammation model induced by central injection of IL-1β, EPA dietary supplementation ameliorated microglia and astrocytic activation in the hippocampus [108].…”
Section: Discussionmentioning
confidence: 92%
“…These cellular changes were associated with the amelioration of spatial and recognition memory skills in these animals [73]. Hippocampal astrogliosis was also reduced by a LCPUFA combination of DHA, EPA and n-3 docosapentaenoic acid (DPA) supplementation in aged male mice with forebrain cholinergic depletion, in correlation with recognition memory restoration [107]. The beneficial effect of n-3 LCPUFA in reverting the inflammatory scenario appears to be also achieved with specific individual n-3 LCPUFA species; thus, in a rat neuroinflammation model induced by central injection of IL-1β, EPA dietary supplementation ameliorated microglia and astrocytic activation in the hippocampus [108].…”
Section: Discussionmentioning
confidence: 92%
“…Thus, animal models with a specific lesion of BFCNs are adequate for the study of dementia symptoms related with the prodromal stages of AD. The 192IgG-saporin lesion model in rat, first described in 1991, causes cognitive deficits in memory tasks such as the novel object recognition test, Morris water maze, and passive avoidance. , Consequently, it has been used in numerous studies as a model of memory impairment and neurodegeneration. …”
mentioning
confidence: 99%
“…Omega-3 PUFAs play important roles in preventing neurodegeneration by inhibiting neuroinflammation, promoting synaptic plasticity and neurogenesis, facilitating nervous system repair, and protecting against the reduction of gray matter volume and the decline of white matter integrity ( 19 , 142 , 143 ). Studies have found that omega-3 PUFAs can promote the proliferation and migration of nerve cells, and inhibit apoptosis ( 48 , 144 ). According to a ten-year follow-up study, higher levels of plasma EPA and DHA are associated with a slower decline in medial temporal lobe volume and a lower risk of dementia in older adults ( 145 ).…”
Section: Possible Anti-depressant Mechanisms Of Action Of Omega-3 Pufasmentioning
confidence: 99%